(untitled) (Human Factors in Design, 2022)
The working day of ROCAM police officers in the State of São Paulo has a high intensity and requires a high level of performance. To analyze the ergonomics present in the day-to-day life of the police officers, a questionnaire was conducted where a sample was obtained with 120 answers with the objective of collecting quantitative and qualitative data in relation to the profession. Ergolândia software was used to perform an angular analysis of the position of the body members during the activity, then the application of methods that help to evaluate working conditions was used. The results of the applied methods indicated the existence of an imminent risk in relation to working conditions and indicated that adjustments should be made to the activity, to avoid future physical damage to the police. From the analyses it is possible to conclude that the main offending person during the work is the motorcycle, in which it does not have customized adjustments for each type of person.